2015
DOI: 10.1371/journal.pone.0138904
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Oxidative Stress Markers in Depression

Abstract: ObjectStudies have suggested that depression was accompanied by oxidative stress dysregulation, including abnormal total antioxidant capacity (TAC), antioxidants, free radicals, oxidative damage and autoimmune response products. This meta-analysis aims to analyse the clinical data quantitatively by comparing the oxidative stress markers between depressed patients and healthy controls.MethodsA search was conducted to collect the studies that measured the oxidative stress markers in depressed patients. Studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
313
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(337 citation statements)
references
References 104 publications
20
313
0
4
Order By: Relevance
“…Thirdly, it may cause oxidative stress dysfunction in the brain including abnormal total antioxidant capacity, antioxidants, free radicals, oxidative damage and autoimmune response products (Liu et al, 2015 for a review). These effects may contribute to impaired mood, cognition and perception, all of which are associated with depression .…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, it may cause oxidative stress dysfunction in the brain including abnormal total antioxidant capacity, antioxidants, free radicals, oxidative damage and autoimmune response products (Liu et al, 2015 for a review). These effects may contribute to impaired mood, cognition and perception, all of which are associated with depression .…”
Section: Introductionmentioning
confidence: 99%
“…Folic acid supplementation in patients with MDD may enhance their response to treatment through the reduction of homocysteine serum levels. There is also evidence to indicate that oxidative stress and reduced antioxidant function play a role in depression (45). Previous studies have well demonstrated that folic acid increases the total antioxidant capacity in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Excess production of ROS can lead to a situation of oxidative stress, which is responsible for many pathological processes and has an impact on the body's aging process. Oxidative damage has been implicated in the cause of many diseases, including cardiovascular disease, diabetes, neuronal degeneration, depression, cancer and probably aging [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…To protect cells against oxidative stress, certain low molecular weight antioxidant molecules, either water-soluble (e.g., ascorbic acid) or lipid-soluble (e.g., vitamin E), are present in extracellular fluids [2,3]. The concentrations of antioxidants can be measured separately but this is not practical since their antioxidant effects are additive.…”
Section: Introductionmentioning
confidence: 99%